Corporate Liquidity and Capital Structure - Anderson, Ronald W.; Carverhill, Andrew (Review of Financial Studies, 2012)
[We solve for a firm's optimal cash holding policy within a continuous time, contingent claims framework using dividends, short-term borrowing, and equity issues as controls assuming mean reversion of earnings. Optimal cash is non-monotone in business conditions and increasing in the level of long-term debt. The model matches closely a wide range of empirical benchmarks and predicts cash and leverage dynamics in line with the empirical literature. Firm value is quite insensitive to changes in the level of long-term debt. The model has interesting implications for asset substitution, hedging, and pecking order. Growth opportunities do not greatly affect cash holding policy.]